Influência do comprimento do pino de fibra de vidro na resistência à fratura de raízes fragilizadas - Junqueira, Rafael Binato [UNESP] (2015)
The aim in this study was to evaluate, in vitro, the influence of glass fiber posts of different lengths on the fracture resistance of roots submitted to different weakening protocols. Ninety bovine roots, of same dimensions, were endodontically treated and randomly distributed in 9 groups (n =10), according the weakening protocol (NW - non-weakened; MW - medium-weakened; HW - hard-weakened) and the post length (7 mm; 9 mm e 12 mm). The canals were prepared for the posts and, on the weakened roots, they were individualized with composite resin A chemically activated resin cement was used in all posts. After luting, coronary reconstruction was conducted with composite resin, based on standardized silicon matrix. To reproduce physiological mobility, root portion was covered by polyether and embedded in polyurethane. The thermomechanical cycling was realized under a load of 88 N at 1.200.000 cycles, with a frequency of 3.8 Hz. For the resistance of fracture analysis, the specimens were placed at 45 ° in a universal testing machine, with a load-cell of 100 Kgf, with speed of 1mm/min. After mechanical essay, the specimens were analyzed by stereomicroscope to classify the failure mode (reparable/irreparable). Numerical values (n = 10) obtained for specimens' fracture were subjected to statistical analysis ANOVA two-way and Tukey test (5% of significance). The frequencies of failure mode were compared by chi-square test. ANOVA showed that the association between length and weakening was statistically significant (p < 0.05). The post-hoc Tukey's test revealed that this difference was between NW and HW roots for posts of 12-mm in length. Chi-square test indicated association between failure mode and the length and weakening factors. It was concluded that highly-weakened roots with longer posts had lower fracture resistance values, as catastrophic mode was more predominant